Investigating the impact of abiotic stresses on the growth and persistence of plantain (Plantago lanceolata L.) within grazed mixed pastures : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science at Massey University, Palmerston North, New Zealand - Wilson, Samuel (Massey University, 2025)
The New Zealand dairy industry has identified plantain (Plantago lanceolata L.) as a tool to mitigate nitrogen losses from perennial ryegrass (Lolium perenne L.) based pastures, however reports of variable pasture plantain contents (dry matter basis) and poor persistence within grazed mixed pastures have led to industry concern over its viability. There is anecdotal evidence that the persistence of plantain within dairy pastures is negatively impacted by waterlogging and treading damage from livestock, however there is little scientific literature relevant to these issues. This research aimed to answer the following research question: What are the impacts of waterlogging and treading damage on plantain growth and survival within mixed dairy pastures? This thesis includes a series of experiments conducted between 2021 and 2024. In a glasshouse, the performance of plantain under waterlogging was evaluated against perennial ryegrass. Plantain growth was particularly sensitive to waterlogging, however the survival of plantain under waterlogging suggested that plantain possesses some waterlogging tolerance. In contrast, perennial ryegrass proved to have an enhanced ability for coping with, and recovering from, waterlogging stress. These findings suggest that while waterlogging may cause limitations to plantain growth, there is no evidence to suggest that waterlogging alone could cause a major decline in plantain density within mixed pastures. Rather, waterlogging could undermine the ability of plantain to compete with perennial ryegrass in mixed pastures. The impact of treading damage on plantain regrowth and survival was investigated in two field experiments. In a small-plot study, treading damage was simulated on separate plantain and perennial ryegrass pastures using a novel treading device. Damage by the treading device, in late spring, immediately reduced the herbage accumulation rate of both plantain and perennial ryegrass pastures by 30%, however neither plantain content nor density were reduced as a consequence of the damage. In a larger, two-year experiment, on a mixed plantain + perennial ryegrass pasture, early spring treading damage by dairy cows reduced pasture growth by 50% and 75% during the early spring periods of year one and two, respectively. Plantain content tended to be lower in damaged plots during early spring in both years, before recovering throughout summer, although this effect was more pronounced during year one. Treading damage caused a reduction in plantain shoot yield (leaf + petiole) and density in year one, however the negative effects of the damage on plantain growth were short-lived and subsided throughout the first year of the experiment. Treading damage in early spring in year two did not significantly impact plantain content or density. An observed reduction in plantain shoot density in late spring in year two was possibly caused by shading from perennial ryegrass. Taken together, these results suggest that treading damage in early spring is unlikely to be a primary cause of plantain content decline within mixed pastures, although it might contribute to temporary reductions in plantain content during spring, particularly in newly established swards. It is possible that treading damage could reduce the ability of plantain to compete with perennial ryegrass in mixed pastures.
Keywords: mixed pastures, dairy production, persistence, grassland science; 300404 Crop and pasture biochemistry and physiology